Fractal characterizations of energetic Si ions irradiated amorphized‐Si surfaces. (22nd May 2019) - Maity, G.; Ojha, Sunil; Sulania, I.; Devrani, K.; Patel, Shiv P.
Abstract : The fractal characterizations of amorphized‐silicon ( a ‐Si) surfaces under low‐energy ion irradiations are presented. The crystalline Si surfaces have been irradiated with Si ions having different energy of 35, 50, 75, and 100 keV at a fixed fluence of 2 × 10 15 ions‐cm −2 . The samples have been characterized by means of using Raman spectroscopy, Channeling‐Rutherford backscattering spectrometry ( C‐ RBS), and atomic force microscopy (AFM) techniques. The ion irradiation leads to the amorphization of Si near surface and subsurface region, as confirmed by Raman and C ‐RBS measurement. The AFM analysis shows that the ion irradiation also leads to the formation of nanodots on the surface and size of the dots increases with increasing of the ion energy. The fractal analysis has been performed using AFM images in order to get the significant evidence about nanodot formations and the correlation inside the surface microstructures. The kinetic roughening and surface smoothening, due to dissipation of kinetic energy of ions through collision cascades of the surface atoms, lead to the formation of dot‐like structures.